1994
DOI: 10.2118/23728-pa
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Sand Arching Mechanics Using an Elasto-Plastic Finite Element Formulation

Abstract: This work is a simulation of sand production mechanics using an elasto-plastic ftnite element formulation. An open vertical well was considered in order to simulate the performance of near-wellbore unconsolidated sand during hydrocarbon production.In the simulation procedure, the assigned values of the initial stress fteld around the wellbore were taken from previous sand arching experiments conducted at the Colorado School of Mines on a similar well conftguration using 20/40 frac sand. The mechanical rock pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The forming process and evolution characteristics of the pressure-arch of a tunnel have received wide attention of scholars and professionals in the world. For examples, Polillo et al conducted a sand arching experiment on a similar well configuration, observed the effect of well excavation on the stability of the surrounding sand [1]. Goel et al found the tunnel size effect on the support pressure was significant in flat-roofed underground openings, and suggested two equations for the associated support pressure estimation [2].…”
Section: State Of the Artmentioning
confidence: 99%
“…The forming process and evolution characteristics of the pressure-arch of a tunnel have received wide attention of scholars and professionals in the world. For examples, Polillo et al conducted a sand arching experiment on a similar well configuration, observed the effect of well excavation on the stability of the surrounding sand [1]. Goel et al found the tunnel size effect on the support pressure was significant in flat-roofed underground openings, and suggested two equations for the associated support pressure estimation [2].…”
Section: State Of the Artmentioning
confidence: 99%
“…The proposed modeling techniques vary from simple, linear elastic analytical solutions 13,14 to complex numerical modeling that accounts for sophisticated material properties 15,16,17,18 and interaction between drilling fluid and formation. 19,20 The simple, linear elastic solutions always gain more popularity as they are relatively easy to implement, require easily obtainable input parameters, are capable of assessing borehole instability risks for most well trajectories, and provide continuous evaluation along the whole borehole trajectory rather than at a single depth.…”
Section: How To Make a Wellbore Stability Analysis For Ubdmentioning
confidence: 99%